Enhancement of employment satisfaction on emotional needs and work persistence - Abdul Majid, Norliza; Mohd Shariff, Abd Rahim; Ahmad, Nor Aniza; Burhanuddin, Nur Aimi Nasuha (Human Resource Management Academic Research Society, 2020)
The satisfaction factors in this study refer to the factors which influence job satisfaction that meet the emotional needs of teachers towards their tasks. The study identifies how job satisfaction can create work excitement and increase the determination to work hard. The findings of this study are focused on job satisfaction which will have a high impact on emotions in influencing the thinking and action of participants. The discussion covers three main job satisfactions namely: i) job satisfaction from student achievement ii) job satisfaction from administrator action and iii) job satisfaction from colleagues cooperation. This qualitative case study is conducted to ensure that the responsibilities need to be done by teachers should be complemented by job satisfaction and the excellent teaching outcomes can shape the quality students. Data sources were obtained from five excellent teachers as research participants. Two instruments, interview protocols and document analysis were used as tools to collect data. In-depth interviews were conducted to obtain detailed information from the participants. The findings was analyzed descriptive and interpretive based on emerging themes and triangulation techniques were conducted to determine the validity and reliability of the results. The findings show job satisfaction is a requirement that needs to be fulfilled because every individual needs internal satisfaction which can encourage ones to achieve the desired goal. The role of students, administrators and colleagues cooperation are the needs to be given priority as inspiration in improving the commitment of teachers to the task being entrusted. Therefore, this study will provide guidance to teacher education programs to plan and implement teachers' professional development efforts by emphasizing the importance of job satisfaction to produce outstanding teachers.